Avaliação da imagem corporal, hábitos de vida e alimentares em crianças eadolescentes de escolas públicas e particulares de Belo Horizonte - Ana Elisa Ribeiro Fernandes (2007)
Objective: to describe body image satisfaction in students from 6 to 18years old from public and private schools in Belo Horizonte and relate it with physical activity, nutrition state, eating habits and sociodemorgaphiccharacteristics. Methodology: it deals of an epidemiologic research (prevalence study). Sociodemographic, weight, height, body mass rate, physical activity, sedentary levels and eating habits data were collected and the body satisfaction was evaluated through the silluete scale. Age was divided into four groups: children (six to nine years), precocious adolescence (10 to 13 years), average adolescence (14 to 16) and late adolescence (17 to 18 years). The sample included 1.183 students between six and 18 years old, enrolled in the Ensino Fundamental and Médio (Grammar and High school) in 16 public schools and fourprivate schools in Belo Horizonte, Minas Gerais. Results: from the body mass index calculation, 5, 2% students were malnourished, 80, 1% were eutrophic, 9, 9% were overweight and 4, 9% were obese. Most students were dissatisfied with their body (62, 6%). From the total, 33, 7% would like to be thinner, 28, 9% would like to be fatter and only 37, 4% were satisfied with their body. In the unvaried analysis there was significant statistical difference for the variable economic class; responsible peoples school level; kind of school; kind of food. The tabagists, thewhites, the students whose responsible people had complete higher level school grade, the students belonging to higher economic classes, the students from private schools, those who ate more fruits, fibers and vegetable and more food rich in saturated fat food would like to be thinner. The blacks, the students whose responsible people had complete first school grade / uncompleted second schoolgrade, the students belonging to the lower economic classes, the students from public schools, those who had very inadequate diet concerning fibers, fruits and vegetables would like to be fatter. Among the students who would like to loose weight, the tabagists had about twice more chances to want to loose weight than those who didnt smoke. Students from private schools had 1,64 times more chances to want to loose weight. Students who had fat rich diet presented almosttwice more chances to want to loose weight. Among the students who would like to put on weight, the chances of students from public schools were almost twice greater than the students from private schools. Those with physical activity had 1,5 times chances to want to put on weight than those with less physical activity. Students with very inadequate fiber, fruit and vegetable diet showed 1, 43 times more chances to want to put on weight. Conclusion: the results showed high percentage of students with body dissatisfaction, starting in a very precocious age. To prevent the development of an unfavorable body image becomes very important, due to the association with food troubles, low esteem, limited psychosocial performance, depression and also obesity.